2022
DOI: 10.1039/d2fo01161a
|View full text |Cite
|
Sign up to set email alerts
|

The different effects of psyllium husk and orlistat on weight control, the amelioration of hypercholesterolemia and non-alcohol fatty liver disease in obese mice induced by a high-fat diet

Abstract: Obesity is a widespread medical problem, for which many drugs have been developed, each with its own limitations. Orlistat, a lipase inhibitor, functions as a fat absorption blocker and is...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 77 publications
2
12
0
Order By: Relevance
“…7(a,b)), which is a marker of gut homeostasis disorders. 38 As expected, compared with the HFD group, LP-HF02 treatment remarkably enhanced the ratio of Bacteroidetes/Firmicutes (Fig. 7(a,b)).…”
Section: Effect Of Lp-hf02 On Intestinal Microbiota In Obese Micesupporting
confidence: 80%
See 1 more Smart Citation
“…7(a,b)), which is a marker of gut homeostasis disorders. 38 As expected, compared with the HFD group, LP-HF02 treatment remarkably enhanced the ratio of Bacteroidetes/Firmicutes (Fig. 7(a,b)).…”
Section: Effect Of Lp-hf02 On Intestinal Microbiota In Obese Micesupporting
confidence: 80%
“…7(a)). Among them, Bacteroidetes and Firmicutes play vital roles in the regulation of energy metabolism in the host 38 . It has been indicated that intestinal microbiota characterized by an increase ratio of Firmicute/Bacteroidetes could more efficiently obtain energy from food 26 .…”
Section: Resultsmentioning
confidence: 99%
“…The body weight of mice was recorded weekly. The final body length was measured for the calculation of Lee’s index as [body weight (g) 1/3 × 1000/body length (cm)]. After 18 weeks, all mice were euthanized after 12 h of fasting. Subsequently, serum was obtained following centrifugation at 3500 rpm and 4 °C for 15 min.…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, psyllium significantly increase concentrations of butyrogenic species including Roseburia , Lachnospira and Faecalibacterium concentrations and associated SCFAs, while also improving immune function [ 156 ]. Interestingly, recent findings suggest that psyllium husk is more effective than orlistat, a lipase inhibitor, in reducing liver cholesterol and TG levels in HFD-induced obesity [ 157 ]. Both psyllium husk and orlistat had beneficial effects on FXR receptor and sterol-27-hydroxylase expression, while regulating levels of important bile acids in the feces.…”
Section: Targeted Microbiota Therapiesmentioning
confidence: 99%